Meningkatkan Kemampuan Berhitung Anak Melalui Media Belajar Ular Tangga Di Kelompok B Tk Al- Alkhairaat Nunu Kota Palu: Improving Children's Counting Ability Through Snakes and Ladders Learning Media in Group B Al-Alkhairaat Nunu Kindergarten, Palu City - Fauziah (ECEIJ (Early Childhood Education Indonesian Journal), 2022)
Learning For early childhood must use concrete and fun objects. One of the fun ways to learn is by using the media. This study aims to improve the ability to count using snakes and ladders media at Alkhairaat Nunu Kindergarten, Palu City. The subjects of this study were the children of Group B2 Alkhairaat Nunu Kindergarten, Palu City. The object of this research is children's numeracy skills including sorting numbers, matching. Addition, and subtraction. This research includes classroom action research (classroom action research). The research instrument used was through guidelines with instrument tests. Analysis of research data using descriptive statistical analysis. The subjects of this study were the children of the B2 group of Alkhairaat Nunu Kindergarten, Palu City. Men's research results showed that there was an increase in numeracy skills from the pretest, cycle I and cycle II. The results of the pretest assessment totaled 144 scores with a percentage of 57.6% increased to 173 with a percentage of 69.2% in the first cycle, then in the second cycle increased by a total of 220 with a percentage of 88.4%. Based on these results, the research has succeeded in achieving the specified indicator, which is more than 80%, so it can be said that the numeracy ability of children in the B2 group of Alkhairaat Nunu Kindergarten in Palu City can be improved using the snake and ladder learning media.